Defining Justice: Restorative and Retributive Justice Goals Among Intimate Partner Violence Survivors - Decker, Michele R. (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) and sexual violence (SV) are drivers of women?s morbidity and mortality yet remain among the most underreported crimes in the United States. Understanding IPV/SV survivors? justice preferences and justice definitions can strengthen violence prevention and response systems. In-depth interviews were conducted with women who experienced past-year IPV (n = 26), to explore their justice preferences and recommendations. Primary themes included accountability, safety, and rehabilitation, with examples within and outside the current justice system, and across restorative and retributive justice frameworks. Women sought accountability through a variety of means. Retributive approaches like incarceration offered accountability as well as fleeting safety, but were critically limited in addressing the root causes of violence and, in some cases, were felt to exacerbate the problem. Women?s expressed needs and preferences centered on restorative aspects of justice, including perpetrator?s acknowledgment of harm, achieving physical safety and stability, and perpetrator rehabilitation through counseling. Paradoxically, women?s safety-related justice goals both encouraged and discouraged their engagement in the formal justice system. The discordance between women?s justice preferences and their perceptions and experiences within the current justice system illustrate complex and difficult trade-offs faced by survivors in achieving physical, social, and economic safety. Moreover, they likely contribute to the low levels of IPV/SV reporting to police. Women?s goals were aligned with restorative justice principles, illustrating the value of this approach. In an era of unprecedented dialogue on justice reform, results provide direction for integrating restorative justice practices to strengthen the justice response to violence against women.